2021
DOI: 10.1093/nar/gkab440
|View full text |Cite
|
Sign up to set email alerts
|

HP1021 is a redox switch protein identified in Helicobacter pylori

Abstract: Helicobacter pylori is a gram-negative, microaerophilic, pathogenic bacterium and a widespread colonizer of humans. H. pylori has developed mechanisms that enable it to overcome the harsh environment of the human stomach, including reactive oxygen species (ROS). Interestingly, up to now no typical regulator dedicated to the oxidative-stress response has been discovered. In this work, we reveal that the inhibitor of replication initiation HP1021 functions as a redox switch protein in H. pylori and plays an impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(39 citation statements)
references
References 82 publications
3
24
0
Order By: Relevance
“…The results demonstrated that HP1021 protected the promoter region of ureAB (5'-CGCTTCTGTTAATCTTAGTAAATCAAAACATTGCTACAA TTACATCCAAC-3'), ranging from −47 to +3 with respect to the transcriptional start site, as previously reported ( 52), overlapping the −10 and −35 consensus sequences (Figure 6B). The HP1021 protected DNA sequence revealed three HP1021 binding boxes harboring five putative reported consensus HP1021 binding sequence in sense and antisense strands (57). These results suggested that multiple HP1021 proteins bound to the promoter region of ureAB, strongly inhibiting ureAB transcription by preventing RNA polymerase binding.…”
Section: Identification Of Hp1021 Binding Site On Ureab Promoter Regionmentioning
confidence: 88%
See 1 more Smart Citation
“…The results demonstrated that HP1021 protected the promoter region of ureAB (5'-CGCTTCTGTTAATCTTAGTAAATCAAAACATTGCTACAA TTACATCCAAC-3'), ranging from −47 to +3 with respect to the transcriptional start site, as previously reported ( 52), overlapping the −10 and −35 consensus sequences (Figure 6B). The HP1021 protected DNA sequence revealed three HP1021 binding boxes harboring five putative reported consensus HP1021 binding sequence in sense and antisense strands (57). These results suggested that multiple HP1021 proteins bound to the promoter region of ureAB, strongly inhibiting ureAB transcription by preventing RNA polymerase binding.…”
Section: Identification Of Hp1021 Binding Site On Ureab Promoter Regionmentioning
confidence: 88%
“…In H. pylori, we found that HP1021 is a transcriptional regulator that responds to AI-2, and to the best of our knowledge, HP1021 is the first transcriptional regulator identified in H. pylori that plays an important role in quorum sensing regulation. HP1021 reportedly regulates the expression of numerous genes, including genes involved in Fe-S assembly, acetone metabolism, DNA replication initiation, and virulence gene cagA (56,57). Quorum sensing in H. pylori might regulate these processes through HP1021 repressed by AI-2.…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrated that OCA reshaped community composition, especially enriching Bacteroides and Helicobacter . Bacteroides is a major BSH bacteria which could deconjugate TCDCA to generate CDCA [ 55 ], and Helicobacter is recognized as a key microbial stimulus of gut ROS production through interaction with intestinal epithelial cells [ 56 ]. To support, these two microbes were positively correlated with liver and ileum ROS levels, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The HP1021 orphan RR acts as an inhibitor of DNA replication by binding to specific sequences within the oriC region, thereby avoiding DnaA- oriC interactions and the unwinding of duplex DNA ( Donczew et al., 2015 ). The DNA binding activity of this RR is affected by both the redox state of its cysteine residues and the presence of divalent metal cations, especially Zn 2+ ( Szczepanowski et al., 2021 ). Hence, the regulator functions as a redox sensor that controls DNA replication, synthesis of Fe-S clusters, acetone metabolism, and response to oxidative stress ( Pflock et al., 2007 ; Donczew et al., 2015 ; Szczepanowski et al., 2021 ).…”
Section: Structural and Functional Diversity Of Tcrs In H P...mentioning
confidence: 99%
“…The DNA binding activity of this RR is affected by both the redox state of its cysteine residues and the presence of divalent metal cations, especially Zn 2+ ( Szczepanowski et al., 2021 ). Hence, the regulator functions as a redox sensor that controls DNA replication, synthesis of Fe-S clusters, acetone metabolism, and response to oxidative stress ( Pflock et al., 2007 ; Donczew et al., 2015 ; Szczepanowski et al., 2021 ). Deletion mutants of this dispensable protein exhibit a small-colony phenotype ( McDaniel et al., 2001 ).…”
Section: Structural and Functional Diversity Of Tcrs In H P...mentioning
confidence: 99%